A Study on the Effects of a Health Education Intervention on Anxiety and Pain During Colonoscopy Procedures. Issue 2 (June 2016) - Hsueh, Feng-Chi; Chen, Chih-Mei; Sun, Chien-An; Chou, Yu-Ching; Hsiao, Szu-Mei; Yang, Tsan
ABSTRACT: Background: Colonoscopy is currently considered the best screening tool in the diagnosis of colon diseases. However, this procedure often causes pain and discomfort in patients, thus reducing patient willingness to undergo and comply with this procedure. Purpose: This study explores the effects of providing procedure-related information to patients receiving colonoscopy in terms of anxiety and pain reduction and identifies factors that influence the pain and anxiety experienced by patients during this procedure. Methods: This study adopted a quasi-experimental design that targeted colonoscopy patients in outpatient clinics. Two hundred thirteen patients were recruited, with 103 patients in the experimental group and 110 in the control group. Participants were recruited between January and April 2011. All of the participants received standard care, and only those participants who were assigned to the experimental group were asked to watch "A Guide to the Colonoscopy Procedure, " a multimedia health informatics CD-ROM. Results: Anxiety scores of the experimental group dropped from 48.7 ± 11.6 to 39.2 ± 8.7 after the intervention. The average pain score of the experimental group was significantly lower than that of the control group (3.8 ± 2.5 vs. 5.0 ± 2.7). Furthermore, trait anxiety, gender, and educational level were identified as the main predictors for state anxiety, and state anxiety was identified as an important predictor for pain during the colonoscopy examination. Conclusions/Implications for Practice: This study found that using a multimedia health informatics CD-ROM to provide information on the colonoscopy procedure effectively reduced the examination-related anxiety and pain of patients.